The relationship of husband's knowledge and attitude to sexual pattern of menopasue wife in the work area of Pematang Raya Puskesmas, Simalungun district - Wilson Samosir; Friska Simanihuruk (Science Midwifery, 2022)
Menopause is a life process that every woman experiences and occurs at an average age of 51 years. Many women are overwhelmed by a sense of anxiety before menopause. The desire for sex usually decreases during menopause, but may recover after symptoms disappear. Even for some husbands menopause is used as an excuse to remarry because the wife is considered to be no longer capable of having sexual relations. This study aims to look at the relationship between knowledge and attitudes of husbands about sexual activity in postmenopausal wives in the working area of the Pamatang Raya Health Center, Simalungun Regency. This study used a correlation descriptive research design , the population and sample in this study were husbands who had menopausal wives in the working area of the Pamatang Raya Health Center, Simalungun Regency, with 34 samples. Sampling using total sampling. The research was conducted in July. The results of the analysis by looking for frequency and percentage showed that the majority of husbands' knowledge about sexual activity in menopausal wives was sufficient, namely 73.5%. And the attitude of husbands about sexual activity in menopausal wives is negative, namely 91.2%. The relationship between knowledge and attitudes was analyzed using the product moment, which obtained a p value of 0.034. There was a significant relationship between knowledge and attitudes of husbands about sexual behavior in postmenopausal wives, and also obtained a value of r = 0.043. The better the husband's knowledge, the better the husband's attitude about sexuality in menopausal wives. It is hoped that it can increase the knowledge of midwives/health workers so that they can provide counseling to married couples about sexual relations during menopause so that they can become the basis for overcoming sexual relations problems faced by married couples during menopause